2018
DOI: 10.5194/aab-61-311-2018
|View full text |Cite
|
Sign up to set email alerts
|

Detection of insertion/deletions (indels) of the <i>ATBF1</i> gene and their effects on growth-related traits in three indigenous goat breeds

Abstract: Abstract. The AT motif-binding factor (ATBF1), also known as zinc finger homeobox 3 (ZFXH3), is necessary for activating the POU1F1 gene; thus, the ATBF1 gene greatly affects the grow traits in animals. The objective of this work was to explore novel indel (insertion/deletion) variations and their associations with growth traits in three native Chinese goat breeds. Two indels within the ATBF1 gene were found in the Shaanbei white cashmere goat (SWCG; n=581), the Guanzhong dairy goat (GZDG; n=334) and the Haina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 34 publications
1
0
0
Order By: Relevance
“…This short region harbors the ZFHX3 gene, also known as ATBF1 , which has a well-known function in humans as a transcription factor that regulates myogenic and neuronal differentiation, with similar effects on Chinese native goat breeds where its polymorphisms influence animal growth rate 41 . As far as found in literature, a study on 3 Chinese local goat breeds confirmed the association of this gene with development traits 42 . In our results, we did not find this HRR island in any of the six Asian breeds.…”
Section: Discussionsupporting
confidence: 69%
“…This short region harbors the ZFHX3 gene, also known as ATBF1 , which has a well-known function in humans as a transcription factor that regulates myogenic and neuronal differentiation, with similar effects on Chinese native goat breeds where its polymorphisms influence animal growth rate 41 . As far as found in literature, a study on 3 Chinese local goat breeds confirmed the association of this gene with development traits 42 . In our results, we did not find this HRR island in any of the six Asian breeds.…”
Section: Discussionsupporting
confidence: 69%